Exploration on the Legal Equity of the Subject of Intelligent Healthcare Responsibility and the Principle of Liability - Yafang QIAN; Zhenliang WANG (Yixue yu zhexue)
The rapid development of intelligent healthcare is profoundly influencing pre-diagnosis, intra-diagnosis, and post-diagnosis stages. However, as medical advancements grow, so do associated risks. Proactive measures are preferable to reactive remedies. Focusing on the most controversial issues in intelligent healthcare: the subject of intelligent healthcare responsibility and the principle of liability, the authors view the ambiguous subject of intelligent healthcare responsibility and the principle of liability as the main obstacles to the effective legal regulation of intelligent healthcare. Based on an analysis of the criteria for selecting the subject of intelligent healthcare liability and the principle of liability, the authors hence propose improvements such as reasonable allocation of the burden of proof, the adjustments and alignment of the existing laws, as well as the optimisation of evaluation standards and institutions.